The Modernization of the Oedipus Myth: Contrasting Cocteau’s The Infernal Machine with Sophocles’ Oedipus Rex - Tanvir , Muhammad Furqan Tanvir (Journal of Research in Humanities, 2023)
The aim of this paper is to explore, by contrasting Sophocles’ Oedipus Rex and Jean Cocteau’s The Infernal Machine, how mythological stories and characters are in their essence archetypes that are exploited by authors in different ages to project different visions of the human situation. Every writer imbibes the influence of his age to a certain degree and if the art of Sophocles is set against that of Cocteau, the dichotomy of moral and philosophical outlook thus established cannot go unnoticed. Written in the twentieth century, Cocteau’s play is in major ways different from the Greek version written more than two thousand years ago in spite of the fact that the plot outline of both remains the same. The contrast will be highlighted in both thematic and structural terms: the former in conceptual differences of heroism, providence, man’s consciousness and destiny, and the latter in the different manipulation of theatrical devices like the chorus and physically evident poetic symbolism. Through recourse to comments made by some literary authors and critics on the characteristic features of the literature of the modern age, it would be shown how The Infernal Machine is to be categorized within it both historically and philosophically.